Uji Efektivitas Aplikasi Serbuk Daun Kemangi (Ocimum basilicum L.) Untuk Mengendalikan Nematoda Meloidogyne Spp. Pada Tanaman Seledri (Apium graveolens) - Khairunissa Khairunissa; Elly Liestiany Liestiany (www.ulm.ac.id, 2026)
Celery plants (Apium graveolens L.) are horticultural commodities with high economic value. In recent years, one of the main problems in celery cultivation in the Landasan Ulin area, Banjarbaru City, is root knot disease caused by the nematode Meloidogyne spp. Infection with this pathogen causes typical symptoms in the form of chlorosis or yellowing of leaves, stunted growth, stunted plants, wilting, and the formation of knots or swelling on the roots. The use of plant-based pesticides is an important alternative to reduce dependence on chemical pesticides. Basil oil is known to have larvicidal activity through a contact poison mechanism on the surface of the larva's body, thanks to its content of the phenolic compound eugenol which is easily absorbed through the cuticle. This study aims to evaluate the effectiveness of the application of basil leaf powder (Ocimum basilicum L.) in suppressing the nematode population Meloidogyne spp. on celery plants. The experimental design used a Completely Randomized Design (CRD) with five treatments and four replications, so that 20 experimental units were obtained, each consisting of three plants. The results showed that the control treatment (K) had an attack rate of 43.34% and was very significantly different compared to other treatments. Administration of 90 g of basil leaf powder was able to reduce the intensity of nematode attacks by up to 5.00%, making it the most effective treatment in controlling Meloidogyne spp.